Mr. putter & tabby smell the roses ebook - Rylant, Cynthia (Mr. Putter & Tabby, 2020)
Adventure is in bloom in this endearing story for early readers from the Newbery Medal-winning author of the Henry and Mudge series! Mr. Putter wants Mrs. Teaberry's birthday to be extra special this year. So how about a trip to the Conservatory to see the beautiful trees and plants and flowers? It will be heavenly. And it is! Mr. Putter and Tabby and Mrs. Teaberry and Zeke sniff the air. They smell the roses. They learn the plant facts. It's the perfect celebration—until Zeke finds the banana tree... "Since the Mr. Putter & Tabby series began, its signature combination of storytelling, wit, and humanity have made it a staple of the beginning reader section."— Booklist